Determination of Cadmium, Copper, Iron, Nickel and Zinc in Turkish Grape Seeds - Tusat, Ekrem; Musa Ozcan, Mehmet; Er, Fatih; Gokmen, Fatma (Asian Journal of Chemistry, 2011)
The rate of heavy metal pollution in some grape seed samples cultivated in Turkey were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). Iron, zinc and copper were found high levels in the seed samples. The highest content in the majority was established as iron. On the contrary, cadmium and nickel were established low concentrations. The cadmium contents had markedly lower. The lowest and the highest cadmium concentrations were 0.12 ppm in the Göküzüm from Konya (Taskent) and 0.49 ppm Nazli sample from Meram (Konya), respectively. Iron contents of grape seeds ranged from 21,65 ppm (Aküzüm) (Hatip- Konya) to 192.16 ppm (Göküzüm) (Taskent-Konya). In addition, Eksikara seed contained 140.45 ppm iron.